(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this study we find out the Alternate formula for production rate. We know the actual Production rate of from the all 60 out comes from we find out from the C programming computation. But the computation for large (more than 5 station un-paced production) un-paced production line is difficult therefore we make an arrangement from this study to design an assembly line production who is working efficiently from this easiest formula.